Production Protocol Standardisation, Macroscopic and Histological Evaluation, and Growth Factor Quantification of Canine Leukocyte-and Platelet-Rich Fibrin Membranes - Caterino, Chiara; Della Valle, Giovanni; Aragosa, Federica; De Biase, Davide; Ferrara, Gianmarco; Lamagna, Francesco; Fatone, Gerardo (Frontiers in Veterinary Science, 2022)
Leukocyte-Platelet-Rich Fibrin (L-PRF) is a second generation of platelet concentrates; it was widely used, as an autologous platelet-based wound sealant and hemostatic agent in surgical wound healing. L-PRF clot or membrane is a solid fibrin-based biomaterial, with a specific 3D distribution of the leukocytes and platelet aggregates. This biological scaffold releases growth factors (i.e., TGF- β1, PDGF-AB, VEGF) and matrix proteins (fibronectin, vitronectin and thrombospondin-1) during the healing process after the application. To the Authors’ knowledge both in human and veterinary medicine a single standardized protocol was not reported. This prospective study aimed to apply Crisci’s L-PRF protocol (30” of acceleration, 2’ at 2700 rpm, 4’ at 2400 rpm, 3’ at 3000 rpm, and 36” of deceleration and arrest) in canine species, evaluate macroscopically and histologically the L-PRF membranes obtained by using Wound Box to standardize the L-PRF protocol in dogs and to evaluate the clinical feasibility of using L-PRF membranes by quantitative in vitro analysis of growth factors over 7 days. One hundred twenty-eight dogs in good general condition with no history of recent NSAIDs intake (15 days of washout) and/or any medication or disease related to coagulation process met inclusion criteria and therefore were enrolled. We obtained 172 membrane L-PRF membranes by 86 dogs: 86 underwent macroscopic and histological analysis, the other 86 underwent ELISA analysis. The Wound Box gave a membrane of mean (±SD) length (cm), width (cm) and weight (g) of 1.97 (±0.89), 0.95 (±0.36), 0.46 (±0.20) respectively. Histology analysis confirmed a well-defined histoarchitecture with 5 layers reproducing density and distribution of blood cells in this biomaterial. Finally, the ELISA assay showed a peak in growth factors at 6 hours after membrane production, followed by a decrease in release at 24 and 72 hours and a second peak in release at 168 hours after production. Statistical analysis of demographic variables and the average of growth factors determined by the ELISA assay did not reveal statistical significance, except for the BCS factor compared with the production of VEGF. Our data confirm the effectiveness of this protocol and of Wound Box to produce canine L-PRF membranes.